Learning to look : a handbook for the visual arts - Taylor, Joshua C. (Chicago : University of Chicago Press, 1957)
The Materials brought together in this book have served for some years, in rather different form, as introduction and handbook of reference to the art portion of the initial humanities course at the University of Chicago. This required course, known as humanities 1, extends over the entire academic year and includes study in music and literature as well as visual arts.
I. An Analysis of the work of arts -- II. Color and Perspective -- III. Some distinctive characteristics within the visual arts -- IV. Some material and techniques of the artist -- V. The Artist and the work of art.
Includes index.
Keywords: VISUAL ARTS